Recognition of cyclic steps in sandy and gravelly turbidite sequences, and consequences for the Bouma facies model. Issue 7 (4th August 2014) - Postma, George; Kleverlaan, Kick; Cartigny, Matthieu J. B.; Mohrig, David
Abstract Preservation of cyclic steps contrasts markedly with that of subcritical‐flow bedforms, because cyclic steps migrate upslope eroding their lee face and preserving their stoss side. Such bedforms have not been described from turbidite outcrops and cores as yet. A conceptual block diagram for recognition of cyclic steps in outcrop has been constructed and is tested by outcrop studies of deep water submarine fan deposits of the Tabernas Basin in south‐eastern Spain. Experimental data indicate that depositional processes on the stoss side of a cyclic step are controlled by a hydraulic jump, which decelerates the flow and by subsequent waxing of the flow up to supercritical conditions once more. The hydraulic jump produces a large scour with soft‐sediment deformation (flames) preserved in coarse‐tail normal‐graded structureless deposits (Bouma Ta), while near‐horizontal, massive to stratified top‐cut‐out turbidite beds are found further down the stoss side of the bedform. The architecture of cyclic steps can best be described as large, up to hundreds of metres, lens‐shaped bodies that are truncated by erosive surfaces representing the set boundaries and that consist of nearly horizontal lying stacks of top‐cut‐out turbidite beds. The facies that characterize these bedforms have traditionally been described as turbidite units in idealized vertical sequences of high‐density turbidity currents, but have not yet been interpreted to represent bedforms produced by supercritical flow. Their large size, which is in the order of 20 m for gravelly and up to hundreds of metres for sandy steps, is likely to have hindered their recognition in outcrop so far.